PARADIGM SHIFT OF WOMEN'S PROPERTY RIGHTS IN INDIA: EVOLUTION, CHALLENGES, AND RECOMMENDATIONS - Sepaha, Priya; Sepaha, Narayani (Mimbar Hukum, 2024)
Abstract This research paper examines the evolution and reform of laws in India, focusing on shifting paradigms on the concept of gender equality specifically regarding women's property rights. The study explores the driving factors behind this paradigm shift triggering the legal reforms, emphasizing the extensive processes and timelines required for significant change. It identifies persistent gaps in these rights, highlighting challenges arising from insufficient implementation, inadequate administrative support, gender inequality and deeply ingrained patriarchal mindsets. While acknowledging legislative advancements like the Hindu Succession (Amendment) Act of 2005, the paper underscores ongoing challenges related to patrilineal inheritance systems, personal laws, and regional variations in reform implementation. The authors advocate for a holistic approach to address implementation complexities and recommend strategies to raise awareness and empower women through equitable property rights enforcement for daughters. Abstrak Artikel ini meneliti evolusi dan reformasi hukum di India, dengan fokus pada perubahan paradigma kesetaraan gender, khususnya hak milik perempuan. Studi ini mengeksplorasi faktor-faktor yang memicu reformasi hukum dan menyoroti proses serta waktu yang diperlukan untuk perubahan signifikan. Penelitian ini juga mengidentifikasi kesenjangan yang masih ada dalam hak-hak tersebut, terutama terkait kurangnya implementasi, dukungan administratif yang lemah, ketidaksetaraan gender, dan pola pikir patriarkal yang kuat. Meskipun terdapat kemajuan legislatif seperti Undang-Undang Amandemen Pewarisan Hindu tahun 2005, tantangan masih berlanjut, termasuk sistem pewarisan patrilineal, hukum pribadi, dan variasi regional dalam penerapan reformasi. Penulis mendorong pendekatan holistik untuk mengatasi masalah implementasi dan merekomendasikan strategi untuk meningkatkan kesadaran serta memberdayakan perempuan melalui penegakan hak milik yang adil bagi anak perempuan.